Determinan Manajemen Laba Pada Perusahaan Manufaktur Consumer Non-Cyclicals Periode 2019-2022 - Meisya Linda (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The purpose of this study is to determine the effect of tax planning, deferred tax expense, and deferred tax assets on earnings management. This research is quantitative research, with secondary data obtained from the Indonesia Stock Exchange (IDX) as the data source. The population in this study comes from manufacturing companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) in the period 2019 - 2022. In this study using purposive sampling method which was selected with certain considerations. There were 13 companies taken as research samples. Based on the results of this study, it shows that tax planning has no significant effect on earnings management, deferred tax expense has no significant effect on earnings management, and deferred tax assets have a significant effect on earnings management.